STRATEGI KEPEMIMPINAN KEPALA MADRASAH DALAM PENDIDIKAN KARAKTER PESERTA DIDIK DI ERA DIGITAL 4.0 - Silawati, Silawati; Hidayati, Dian; Ulya, Lulu Khanifatul; Zakiyah, Retno Himma (Jurnal Ilmiah Pendidikan dan Keislaman, 2023)
The development of technology became something common and had a great influence on society. The digital era 4.0 has a real influence on human life, one example is in the field of education. As a result, it takes leadership that can adapt and take advantage of these technological developments. In the world of education, the principal has a very important and crucial role, because he sets the policy and directs the steps to be followed to achieve the goals of the school. Therefore, a school / madrasah principal needs to develop a strategy in facing the changes in the digital era 4.0. The purpose of this study is to find out how the leadership strategy prepared by the head of the madrasah in character education in the digital era 4.0. This research uses qualitative methods, because the place of this research is in Madrasah Ibtidaiyah Nurul Islam, Parittiga District. The techniques used to obtain data in this study were interviews, observations, and documentation. The object of research is the Leadership Strategy of the Head of Madrasah in Character Education in the Digital Era 4.0. The subjects of this study were the head of the madrasah ibtidaiyah nurul islam as well as teachers, as well as students. It can be concluded that the principal's leadership strategy in character education in the digital era 4.0 is through habituation, discipline, and existing programs